2023
DOI: 10.1186/s12967-023-04161-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids metabolism affects the therapeutic effect of anti-PD-1/PD-L1 in tumor immune microenvironment in clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is a highly invasive and metastatic subtype of kidney malignancy and is correlated with metabolic reprogramming for adaptation to the tumor microenvironment comprising infiltrated immune cells and immunomodulatory molecules. The role of immune cells in the tumor microenvironment (TME) and their association with abnormal fatty acids metabolism in ccRCC remains poorly understood. Method RNA-seq and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This suggests that high CDKL3 expression in ESCC cells may be associated with the activation of autophagy, which promotes macrophage M2 polarization. Lin et al also found that silencing IL4I1 in ccRCC cell lines (786-O, 769-P) could inhibit M2-like macrophage polarization by indirectly co-culturing with M0 macrophages (51). These results suggest that tumor cells with specific altered ge nes mi ght in fl uence immune cell infi ltration and functional polarization.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This suggests that high CDKL3 expression in ESCC cells may be associated with the activation of autophagy, which promotes macrophage M2 polarization. Lin et al also found that silencing IL4I1 in ccRCC cell lines (786-O, 769-P) could inhibit M2-like macrophage polarization by indirectly co-culturing with M0 macrophages (51). These results suggest that tumor cells with specific altered ge nes mi ght in fl uence immune cell infi ltration and functional polarization.…”
Section: Discussionmentioning
confidence: 93%
“…Lin et al. also found that silencing IL4I1 in ccRCC cell lines (786-O, 769-P) could inhibit M2-like macrophage polarization by indirectly co-culturing with M0 macrophages ( 51 ). These results suggest that tumor cells with specific altered genes might influence immune cell infiltration and functional polarization.…”
Section: Discussionmentioning
confidence: 99%
“…[47,48] After conducting extensive investigations on metabolic reprogramming, researchers have come to recognize the significance of FA metabolism in ccRCC. [10,11,13,19] Lin et al [17] developed twenty mRNA signatures associated to fatty acid metabolism in the TCGA dataset. These signatures showed a high prediction ability, as indicated by time-dependent ROC and KM survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Abnormal fatty acid (FA) metabolism has been detected in various cancer forms, such as RCC, breast cancer, gastric cancer, prostate cancer, and lung cancer. [12–18] Notably, the TCGA analysis of ccRCC revealed that metabolic changes play a crucial role in the evolution of ccRCC. [14,19,20] A study and its subsequent analysis revealed a correlation between poorer survival of ccRCC patients and the increased expression of genes related to the pentose phosphate pathway and fatty acid synthesis pathway, as well as the decreased expression of genes related to the TCA cycle.…”
Section: Introdutionmentioning
confidence: 99%
“…First, we have previously performed univariate Cox regression analysis to screen out DE-DRG-FRG associated with OS as model candidate genes. Subsequently, to avoid collinearity and overfitting, the least absolute shrinkage and selection operator (LASSO) were conducted with the R “glmnet” package ( Xu et al, 2023 ) to complete the compression of the coefficients and eliminate genes with zero coefficient ( Lin et al, 2023 ). Finally, we chose the genes with non-zero coefficients to carry on multivariate Cox regression analysis, and the regression coefficients of each gene were obtained.…”
Section: Methodsmentioning
confidence: 99%